1993
DOI: 10.1128/jb.175.17.5384-5394.1993
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of rcsB and rcsC from Escherichia coli O9:K30:H12 and examination of the role of the rcs regulatory system in expression of group I capsular polysaccharides

Abstract: In Escherichia coil K-12, RcsC and RcsB are thought to act as the sensor and effector components, respectively, of a two-component regulatory system which regulates expression of the slime polysaccharide colanic acid (V. Stout and S. Gottesman, J. Bacteriol. 172:659-669, 1990

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 58 publications
(52 reference statements)
3
62
0
Order By: Relevance
“…The histidine kinase-like domain of CyaC (Leu-511 to Leu-729) is similar to the transmitter domain of histidine kinase proteins. This region of CyaC shows 27.9% identity to the LemA protein of Pseudomonas syringae (23), 32.4% identity to the PhoR protein of Shigella dysenteriae (30), 26.0% identity to the RcsC protein of E. coli (24), and 33.3% identity to the PleC protein of Caulobacter crescentus (50). The highly conserved histidine residue of histidine kinase proteins and the aspartate residue of response regulator proteins, both of which are responsible for protein phosphorylation, exist in regions of CyaC (His-524, Asp-59, and Asp-847).…”
Section: Resultsmentioning
confidence: 99%
“…The histidine kinase-like domain of CyaC (Leu-511 to Leu-729) is similar to the transmitter domain of histidine kinase proteins. This region of CyaC shows 27.9% identity to the LemA protein of Pseudomonas syringae (23), 32.4% identity to the PhoR protein of Shigella dysenteriae (30), 26.0% identity to the RcsC protein of E. coli (24), and 33.3% identity to the PleC protein of Caulobacter crescentus (50). The highly conserved histidine residue of histidine kinase proteins and the aspartate residue of response regulator proteins, both of which are responsible for protein phosphorylation, exist in regions of CyaC (His-524, Asp-59, and Asp-847).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, neither an rcsB null mutation nor rcsB overexpression affected expression of the group I capsuleencoding (cps) operon. 114 This suggested that the effect of rcsB overexpression on group I capsule production was indirect. Indeed, it was found that rcsB overexpression induced the galF gene involved in producing sugar nucleotide precursors, and that there was a putative RcsAB-binding sequence (RcsAB box) upstream of galF.…”
Section: 21109mentioning
confidence: 99%
“…In some E. coli strains the production of group I capsule was induced by overexpression of rcsB. 114 However, an rcsB null mutation did not affect capsule production. Furthermore, neither an rcsB null mutation nor rcsB overexpression affected expression of the group I capsuleencoding (cps) operon.…”
Section: 21109mentioning
confidence: 99%
“…The inactivation of the lon gene resulted in overproduction of amylovoran. In E. coli and E. stewartii, the gene coding for the second positive regulator RcsB is localized adjacent to the rcsC gene (16,31,46). The two genes are transcribed in opposite directions, and the coded proteins are proposed to be part of a two-component regulatory system.…”
mentioning
confidence: 99%